Towards More Expressive Problem Structuring: A Theoretical Conceptualization of 'Problem' in the Context of Enterprise Modeling - Bock, Alexander; Kudryavtsev, Dmitry; Kubelskiy, Miroslav (Proceedings of the 20th IEEE Conference on Business Informatics (CBI 2018), 2018)
Dealing with ill-structured problems is a central responsibility of the manager operating in a business environment of complexity and ambiguity. To assist in problem structuring, a number of problem structuring methods have been developed in the ﬁeld of operations research. But the modeling approaches incorporated in existing problem structuring methods lack semantic expressiveness, syntactical precision, and domain-speciﬁc modeling concepts. In contrast, the ﬁeld of enterprise modeling offers a range of semantically rich domain-speciﬁc modeling languages. In this paper, we report on work towards a more expressive problem structuring method that integrates insights from theoretical problem solving research, core assumptions of the ﬁeld of problem structuring methods, and modeling languages from the ﬁeld of enterprise modeling. Speciﬁcally, we present results of a conceptual study of theoretical views of the concept of a problem, we present a meta model conceptualization of ‘problem’ in the context of enterprise modeling, and we illustrate the practical use of the proposed meta model with a case study. The presented conceptualization contributes to the ﬁeld of enterprise modeling by offering a more nuanced ‘problem’ modeling concept than is currently available, and by constituting progress towards a problem structuring method that is more expressive and versatile than existing approaches.